Effect of hippotherapy in the global motor coordination in individuals with Down Syndrome - Valéria Sovat de Freitas Costa; Hudday Mendes da Silva; Monique de Azevêdo; André Ribeiro da Silva; Ludmila Lucena Pereira Cabral; Jonatas de França Barros
Abstract Introduction: Down syndrome (DS) of all genetic syndromes is the most common. In Hippotherapy, three-dimensional movements, provided by horse walking, awaken in the body of children with DS a large amount of sensory and neuromuscular stimuli, which directly interfere with overall development and the acquisition of motor skills. Objective: To analyze the effects of an Hippotherapy program on global motor coordination variables in individuals with DS of both genders and to compare individuals with the same syndrome who do not practice Hippotherapy. Methods: 41 individuals participated in the study, 20 of them practicing Hippotherapy (EG) and 21 who did not practice Hippotherapy (CG). The Körperkoordinations test für Kinder (KTK) test was used, consisting of four tasks: Balance on beams, Single-lever jump, Side-jump and Transfer on platform for analysis of motor coordination for individuals. Results: Comparing the groups, a significant difference (p < 0.01) was observed for the Lateral Leap Motor Quotient, the EG presented a better score (114.10) than the CG (88.47), and also in the Total Motor Ratio (EG = 115.10, GC = 102.47). The individuals that practice Hippotherapy presented better results in the global motor coordination, with significant difference (p < 0.05). In EG, 5% had high global motor coordination, 40% good and 55% normal, whereas in CG only 10% had good global motor coordination and 90% normal global motor coordination. Conclusion: It can be emphasized that equine therapy presents benefits of improvement in global motor coordination. Specifically in tasks such as the balance beam, single jump and side jump, besides global motor coordination.